Genotypic and phenotypic characterization of Staphylococcus aureus in recurrent tonsillitis patients and molecular detection of resistance gene (mecA) and biofilm formation gene (ica) in Sulaimani Province - Omar, Ari Hussein Karim (Sulaimani Journal for Pure and Applied Sciences, 2025)
Methicillin-resistant Staphylococcus aureus (MRSA) demonstrates resistance to several frequently used antibiotics. Recurrent tonsillitis (RT) is a common inflammation of the palatine tonsils, typically induced by bacterial infection. This study aimed to identify MRSA in patients with recurrent tonsillitis by utilizing both phenotypic and genotypic techniques, including molecular detection of 16S rRNA and the mecA resistance gene, and biofilm formation screening by a 96-well microtiter plate test with detection of icaA and icaD genes. A total of 69 superficial throat swabs were collected from individuals diagnosed with recurrent tonsillitis infections. Among them, 36 (52.17%) tested positive for S. aureus, including 14 (38.88%) MRSA and 22 (61.11%) methicillin-sensitive S. aureus (MSSA). Fifty percent of MRSA isolates were multidrug-resistant (MDR), and 72.72% of MSSA isolates also had MDR characteristics. All isolates exhibited complete resistance to penicillin (100%) while demonstrating full susceptibility to vancomycin (100%). Most MRSA isolates (92.85%) showed susceptibility to ciprofloxacin, except for one strain (P11), whereas only 45.45% of MSSA isolates demonstrated susceptibility. Biofilm generation was observed in 97.22% of isolates, signifying a robust ability for persistence and antibiotic resistance. These data underscore the necessity of employing culture-guided antibiotic treatment for recurrent tonsillitis to guarantee suitable antimicrobial selection. Fluoroquinolones had significant efficacy against S. aureus isolates, indicating their potential use in the culture-based treatment of recurrent tonsillitis. The significant occurrence of biofilm-forming multidrug-resistant strains highlights the necessity for biofilm-targeting techniques to improve treatment efficacy and diminish infection recurrence.
Keywords: (MRSA); (MDR); (Biofilm); (Tonsillitis); (ica gene); (16 S rRNA)